Prayer for protection : a comparative perspective on the Psalms in relation to Lozi traditional prayers - Kamuwanga, Liswaniso (Old Testament essays, 2008)
A comparative analysis of African Traditional Religion and the Old Testament detects proximity and distance amid the two religions. Microcosmic similarities in prayer for protection between biblical psalms and Lozi prayer traditions confirm closeness in religious experience during times of danger between ancient Israelite society and contemporary African tribal societies. Further, these similarities provide concrete points for dialogue between African Traditional Religion and biblical psalms. Inversely, differences underscore the uniqueness of prayer for protection in each of the biblical and African traditions.